ANALISIS FAKTOR-FAKTOR PENENTU PERSISTENSI LABA - Fanani, Zaenal (Jurnal Akuntansi dan Keuangan Indonesia, 2010)
This research is aimed to examine and find out empirical evidence of the influence of cash flow volatility, magnitude of accrual, sales volatility, leverage, and operating cycle on earnings persistence. Samples used in this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) during period 2001-2006. Total samples are 141 companies. The data are collected using purposive sampling method. The analysis of this research employs multiple regression. Results show that cash flow volatility, magnitude of accrual, sales volatility, leverage have significant effect on earnings persistence, but operating cycle do not have significant effect on earnings persistence.